1996
DOI: 10.1007/bf01092517
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed protein: What does the future hold?

Abstract: Cottonseed protein has the potential to increase the world's food supply while decreasing the incidence of malnutrition among the world's hungry. Nutritionally, cottonseed flour compares favorably to other animal and vegetable protein sources, as it is low in fat and contains a substantial amount of high biological value protein. Animal studies, as well as human research, using gossypol-free glandless cottonseed flour have shown that cottonseed protein promotes growth, increased weight gain, and a positive nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Owing to its high protein value for animals (Alford et al, 1996) as well as low market price in comparison with other legumes and fish meal, cottonseed meal (CSM) consequently has an immense potential for incorporation in high-protein aquafeeds. Lee et al (2006) summarized a series of studies in rainbow trout where CSM replaced fish meal entirely over the 3-year period without significantly impacting growth rate of female and male rainbow trout.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high protein value for animals (Alford et al, 1996) as well as low market price in comparison with other legumes and fish meal, cottonseed meal (CSM) consequently has an immense potential for incorporation in high-protein aquafeeds. Lee et al (2006) summarized a series of studies in rainbow trout where CSM replaced fish meal entirely over the 3-year period without significantly impacting growth rate of female and male rainbow trout.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the 44 million metric tons (MT) of cottonseed (9.4 million MT of available protein) produced each year could provide the total protein requirements of half a billion people for 1 year (50 g/day rate) if the seed were safe for human consumption. Thus, gossypol-free cottonseed would significantly contribute to human nutrition and health, particularly in developing countries (3)(4)(5), and would help meet the requirements of the predicted 50% increase in the world population in the next 50 years.…”
mentioning
confidence: 99%
“…After the discovery of a glandless mutant (8), several breeding programs were launched in the U.S., Africa, and Asia to transfer the glandless trait into commercial varieties to produce gossypol-free cottonseed (9)(10)(11). These programs provided cottonseed that could be fed to monogastric animals that use feed more efficiently and was even deemed safe for human consumption (5,11). Cottonseed compared favorably as a source of protein to other traditional food sources in several human nutrition studies (3,5,11).…”
mentioning
confidence: 99%
“…Cottonseed kernels contain about 38% lipid and 39% proteins. The incorporation of cotton flour into animal feed gave very good results, and studies carried out in Africa, India, Peru, France and the USA showed that cottonseed proteins can also be used to improve nutritional and functional properties of human food (Marquie 1987, Bourely 1987, Alford et al 1996. The utilization of this important protein and oil source is still limited because gossypol is noxious for monogastric animals, and particularly toxic to humans.…”
mentioning
confidence: 99%